Uji Aktivitas Antibakteri dan Antioksidan Ekstrak Pigmen Klorofil Rumput Laut Caulerpa racemosa (Forsskal) J.Agardh - Lisiard Dimara; Tien Y.B Yenusi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
The determination of antimicrobial and antioxidant activities of Chlorophyll pigment of Caulerpa racemosa (Forsskal) J.Agardh is described in this study. The aim of the study was to find out the effectiveness of chlorophyll extract in inhibiting growth of Staphylococcus aureus and Escherichia coli. Paper disc method was used to study the hampering the ability of chlorophyll toward both bacteria, and the DPPH (1,1-difenil-2-dipikrilhidrazil) method was used to find out the antioxidant activity. The result showed that extract chlorophyll can inhibit the growth of both bacteria at the concentration of 100% with the inhibition diameter zone 2.170 cm and 2.100 cm respectively. Whereas the IC50 of the chlorophyll is 2350.3 ppm can be served as an antioxidants. Key words: antibacterial, antioxidants, chlorophyll, Caulerparacemosa (Forsskål) J.Agardh.